ACOEM Guidelines Independent Medical Examinations and Consultations - Christopher H. Stewart-Patterson; Charl Els; Ronald Zipper; Douglas W. Martin; Barry Gelinas; Kurt T. Hegmann (Journal of Occupational & Environmental Medicine, 2026)
This guideline offers an overview of independent medical examinations and consultations. These typically occur in complex medical cases requiring an independent, non-partisan opinion or a re-assessment of a diagnosis. The legal requirements regarding independent medical examinations vary by jurisdiction, but it is critical that physicians performing these examinations or consultations both be sufficiently experienced in the area of inquiry and abide by strict ethical standards. A comprehensive consultation or independent medical examination report contains specific elements, generated through a deliberate process and based on the highest-quality evidence. The report should be of sufficient rigor, quality, and clarity to adequately demonstrate the information and decision-making process underpinning the performing physician’s ultimate conclusions.